Estimation of the efficiency of partial case of heat and mass transfer processes between heat pumps and moving substance: Part 4 - Kshevetsky, O.S.; Cherkez , R.G.; Mazar , Yu.I. (Journal of Thermoelectricity, 2023)
A theoretical model is presented for evaluating the efficiency of the partial case of processes in which there is thermal contact of the moving substance (or at least a part of this moving substance) with the heat-absorbing and heat-emitting heat exchange parts of at least two heat pumps for the case of heating the moving substance in its input flow by all separately taken thermoelectric heat pumps. Mathematical expressions for relevant estimation calculations and examples of the results of such calculations are given.